Some Curvature Properties on Lorentzian Generalized Sasakian-Space-Forms - Rongsheng Ma; Donghe Pei (Advances in Mathematical Physics)
In this paper, we investigate the Lorentzian generalized Sasakian-space-form. We give the necessary and sufficient conditions for the Lorentzian generalized Sasakian-space-form to be projectively flat, conformally flat, conharmonically flat, and Ricci semisymmetric and their relationship between each other. As the application of our theorems, we study the Ricci almost soliton on conformally flat Lorentzian generalized Sasakian-space-form.